Minimum Detectable Activity of Pb-210 in Skull From In vivo Measurements: Insights From the Literature - Meng, Xiangpeng; Liu, Yuanyuan; Wu, Bin; Cheng, Jianping; Wang, Li; Wang, Yu; Su, Ning (Frontiers in Energy Research, 2021)
To address the urgent need for the retrospective assessment of the health conditions of people with a history of appreciable radon exposure, a novel technique that directly measures the characteristic γ-rays emitted from Pb-210 in the living skull was developed. Since the first pioneering study in 1968, this technique has experienced continued advancement over more than half a century, where the limit of detection of Pb-210 is a common criterion to assess the performance of the measuring devices. However, researchers have defined the limit of detection in assorted ways, and the measurement conditions often greatly differ from study to study, both of which significantly challenge interstudy comparisons and obscure how various factors make their impacts. In this work, we reanalyze the reported results in the literature according to the minimum detectable activity (MDA) defined by Currie and investigate the effects of key elements therein. Firstly, we focus on the reported background count rates and analyze their dependence on detector’s energy resolution and active area. Secondly, we turn to the reported calibration factors and conduct analysis in the same manner. Thirdly, we calculate MDA for each study and monitor its dependence on the active area of detector and measurement duration. In the limit of the largest achievable active area (∼75000 mm2), it is found that the asymptotic MDA is approximately 6 (4) Bq and 15 (11) Bq under 30 (60) min measurement using NaI-CsI scintillator and HPGe semiconductor detectors, respectively. Finally, we discuss these asymptotic MDA in the context of estimated Pb-210 activity in the skull resulted from a hypothetical history of radon exposure.